Teachers’ Perceptions and Practices on the Integration of Gender Issues in Teaching English at Islamic Secondary School - Wulansari Wulansari; Nuskhan Abid (Universitas Pahlawan Tuanku Tambusai, 2026)
The integration of gender issues in teaching English as a Foreign Language (EFL) plays a crucial role in Islamic schools, as it combines religious values with principles of social justice. This study aims to investigate how EFL teachers integrate gender literacy in Islamic schools (madrasah). The method used was a qualitative case study involving three teachers in Kudus Regency. Data were obtained through interviews, observations, and document analysis, which were then analyzed thematically. The results revealed four main themes: equality, justice, sensitivity, and non-discrimination. The teachers' understanding is based on Islamic values such as justice and compassion, which are reflected in equal participation, the use of gender-neutral language, materials free from stereotypes, and objective assessment. The implications of this study emphasize the importance of teacher training and the development of teaching materials focused on gender literacy in Islamic schools or madrasah.